Task reminder by SMS - Mohd Faizal, Zainal (2005)
For the time being, task load is the common problem that been face by many people until they forgot about what to do next according to the schedule that has been given.So, it is a needed to create a mechanism to ensure the entire task will be inform to the person to avoid from late or missed .Task Reminder by SMS is an application that will be build in order to help users to manage the entire task that has been scheduled. The focus of this project will be concern on development of SMS structure that contains on how the SMS can be send and receive successfully. This project also will try to give some priority to create at least one networking element to ensure the system capable to communicate with device (Mobile Phone). The Application will be build as an application that been connected to the Mobile Phone because it is easier to give some alert because of the user always bring along their Mobile Phone together whenever they are. The user only need enter all the tasks, functions, appointment and any important date to the system and then the user will asked to set the priority based on the suitability. Then the system will send a SMS alert to remind the user that the time for occurrence is coming. Therefore, the user will always realize and always get ready in order to prevent any problem occur and then be able to achieve objectives easily. The System Development Life Cycle (SDLC) has chosen to perform on this project containing five phases. All the phases need to be done continuously until the project finished and the output successfully generated. The output would be come out with a system that will function as a platform to manage all the task and sending SMS reminder to the user.